Soveršenstvovanija nadëžnosti vypolnenija obmenov predmetami v gruppovych upražnenijach chudožestvennoj gimnastiki sredstvami sportivnoj igry - Medvedeva, E. K.; Suprun, A. A.; Borisova, V. V.; Titova, A. V. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
This article concerns the issues of improving reliability when exchanging apparatuses in rhythmic gymnastics group routines. The content side of the sports game - Ringo, which, according to the structure of motor actions, is similar to the interactions of gymnasts in group routines, is revealed. On the basis of the carried-out research the possibility of using this training tool in the process of improving the exchange of apparatuses in group routines in rhythmic gymnastics and improving the reliability of their execution in the conditions of competitive activity has been proved. The authors offer approved methods of special training with apparatuses based on implementing the Ringo game, which is aimed at the optimization of the process of training of sportswomen in group routines in rhythmic gymnastics.